Carbon and oxygen minibeam radiation therapy: An experimental dosimetric evaluation - Immaculada, Martínez‐Rovira; Brons, Stephan (Medical physics, 2017)
Purpose To perform dosimetric characterization of a minibeam collimator in both carbon and oxygen ion beams to guide optimal setup geometry and irradiation for future radiobiological studies. Methods Carbon and oxygen minibeams were generated using a prototype tungsten multislit collimator presenting line apertures 700 ?m wide, which are spaced 3500 ?m centre?to?centre distance apart. Several radiation beam spots generated the desired field size of 15 ? 15 mm2 and production of a 50 mm long spread out Bragg peak (SOBP) centered at 80 mm depth in water. Dose evaluations were performed with two different detectors: a PTW microDiamond single crystal diamond detector and radiochromic films (EBT3). Peak?to?valley dose ratio (PVDR) values, output factors (OF), penumbras, and full width at half maximum (FWHM) were measured. Results Measured lateral dose profiles exhibited spatial fractionation of dose at depth in a water phantom in the expected form of peaks and valleys for both carbon and oxygen radiation fields. The diamond detector and radiochromic film provided measurements of PVDR in good agreement. PVDR values at shallow depth were about 60 and decreased to about 10 at 80 mm depth in water. OF in the center of the SOBP was about 0.4; this value is larger than the corresponding one in proton minibeam radiation therapy measured using a comparable collimator due to a reduced lateral scattering for carbon and oxygen minibeams. Conclusions Carbon and oxygen minibeams may be produced by a mechanical collimator. PVDR values and output factors measured in this first study of these minibeam radiation types indicate there is potential for their therapeutic use. Optimization of minibeam collimator design and the number and size of focal spots for irradiation are advocated to improve PDVR values and dose distributions for each specific applied use.